1998
DOI: 10.1161/01.cir.97.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Body Surface Mapping During Pacing at Multiple Sites in the Human Atrium

Abstract: Use of the P-wave morphology on the 62-lead surface ECG in patients with normal biatrial anatomy allows separation of the origin of ectopic RA impulse formation into one of 17 different endocardial segments with an approximated area size of 3.5 cm2. This database of paced P-wave integral maps provides a versatile clinical tool to perform detailed noninvasive localization of right-sided atrial tachycardia before radiofrequency catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 33 publications
2
37
0
2
Order By: Relevance
“…The minimum potentials for the first 60 ms in CCW CTI-AFL appeared mainly at the left lower anterior chest, whereas those in CW CTI-AFL appeared at the center of the anterior chest (Figure 4A), corresponding to the area of the coronary sinus ostium and lower RA free wall, respectively. 20 Thereafter, the BSM pattern of CTI-AFL was completely reversed with CCW or CW rotation for the first half of the flutter cycle length, consistent with biphasic polarity in the inferior leads of ECG and discordant polarity of leads V1 and V5 in CTI-AFL.…”
Section: Bsm Characteristics During Iartmentioning
confidence: 68%
“…The minimum potentials for the first 60 ms in CCW CTI-AFL appeared mainly at the left lower anterior chest, whereas those in CW CTI-AFL appeared at the center of the anterior chest (Figure 4A), corresponding to the area of the coronary sinus ostium and lower RA free wall, respectively. 20 Thereafter, the BSM pattern of CTI-AFL was completely reversed with CCW or CW rotation for the first half of the flutter cycle length, consistent with biphasic polarity in the inferior leads of ECG and discordant polarity of leads V1 and V5 in CTI-AFL.…”
Section: Bsm Characteristics During Iartmentioning
confidence: 68%
“…Some studies reported that P wave morphology was mainly determined by the septal and right atrial lateral wall activation sequence during stimulation. 12,16,17 We found that P wave morphology, especially the terminal portion is mainly determined by the direction of the left atrium activation sequence, and the left atrium activation sequence is mainly determined by the site of the earliest right atrium activation and the interatrial connection which is the nearest to the site. The interatrial connections are formed of Banchmann's Bundle (BB), the fossa ovalis, and CS.…”
Section: Discussionmentioning
confidence: 89%
“…Multilead body surface potential mapping can be used to help localize the tachycardia site of origin. 118 …”
Section: Diagnosismentioning
confidence: 99%